ROC analysis determines optimal cutoff and doubtable interval of the Bath ankylosing spondylitis metrology index in a multicenter case control study - Genggeng Guo; Juanjuan He; Jianwen Liu; Xiaoye Yan; Meng Zhou; Chenmin Wu; Diantian Lin; Zhihan Chen; Qing Yan; Fei Gao; Zugang Xie; Feng Huang; et al. (Scientific Reports)
Abstract In clinical practice, the Bath Ankylosing Spondylitis Metrology Index (BASMI) score of healthy individuals is more than zero. However, the lower limit of the BASMI score range for patients with ankylosing spondylitis (AS) is 0, which is inconsistent with that observed in actual clinical settings. Based on findings from a multicenter case-control study, the receiver operating characteristic (ROC) curve was used to determine the optimal cutoff value and doubtable value interval of BASMI, thereby providing a reference to facilitate the evaluation of patients with AS.Patients with AS and healthy controls were recruited, and their demographic characteristics were examined. Spinal mobility was assessed by our standardized and trained measurement team. We used the SPSS26.0 statistical software to categorize the pertinent BASMI scores of the patients and healthy controls by age and sex. We subsequently prepared the BASMI ROC curve, calculated the Youden index, and determined the optimal cutoff value and doubtable value interval. In the present study, 246 patients with AS (patient group) and 246 healthy controls (control group) were recruited. Only three (0.9%) and four (1.18%) individuals in the control and patient groups had a BASMI score of 0, respectively. The optimal cutoff value of BASMI in the general population was 1.5 points, the doubtable value interval was 0.7–2.1 points, and the area under the ROC curve was 0.867 (95% confidence interval, 0.835–0.899; P < 0.001). The optimal cutoff value of BASMI was determined as part of a preliminary analysis.A BASMI score > 1.5 may signal spinal mobility limitations; however, its clinical relevance requires validation against functional and structural progression endpoints.Furthermore, when the BASMI score of an individual range from 0.7 to 2.1, it is crucial to determine whether the individual has AS.